Analisis Dan Perancangan Sistem Informasi Manajemen Pendidikan Dan Pelatihan Pada Pusdiklat Perpustakaan Nasional Menggunakan TOGAF - Yudhi Trisna Atmajaya; Wisnu Ananta Kusuma; Irman Hermadi (Jurnal Pustakawan Indonesia, 2016)
Information and communication technology (ICT) has been implemented in almost every division at the National Library. This implementation is supported by Undang-Undang Nomor 43 tentang Perpustakaan. The aim of using ICT is to improve working performance and services of National Library. Pusat Pendidikan dan Pelatihan (Pusdiklat) is one of divisions that has not fully implemented ICT yet to increase the training quality and quantity, therefore management information system is required to support decision making related to the training. This research objective is to design a management information system using enterprise architecture framework, TOGAF. TOGAF provides a flexible framework to accommodate management information system design according to the organization’s vision, mission and goals. This research yielded a blueprint of management information system of training’s program and evaluation. It is expected that this blueprint could be used to guide the development of management information system in Pusdiklat.Keyword: Enterprise Architecture Framework, Management Information System, TOGAF, UML